Substrate cycling between gluconeogenesis and glycolysis in euthyroid, hypothyroid, and hyperthyroid man. - Shulman, G I (1985)
Substrate, or futile cycles, have been hypothesized to be under hormonal control, and important in metabolic regulation and thermogenesis. To define the role of thyroid hormones in the regulation of substrate cycling in glycolysis and gluconeogenesis, we measured rates of cycling in normal (n = 4), hypothyroid (n = 5), and hyperthyroid (n = 5) subjects employing a stable isotope turnover technique. Glucose labeled with deuterium at different positions (2-D1-, 3-D1-, and 6,6-D2-glucose) was given as a primed-constant infusion in tracer doses, and arterialized plasma samples were obtained and analyzed by gas-chromatography mass-spectrometry for the steady state enrichment of glucose that was labeled at the various positions. The rate of appearance (Ra) was then calculated for each isotopic tracer. The difference between the Ra determined by 2-D1-glucose (Ra2) and the Ra determined by 3-D1-glucose (Ra3) represents the substrate cycling rate (SCR) between glucose and glucose-6-phosphate. The difference between the Ra determined by 3-D1-glucose (Ra3) and the Ra determined by 6,6-D2-glucose (Ra6) represents the SCR between fructose-6-phosphate and fructose-1,6-diphosphate. The difference between Ra2 and Ra6 represents the combined SCR of both cycles. In normal subjects (serum thyroxine [T4] = 8.4 +/- 1.2 microgram/dl (all expressions, mean +/- SD), n = 4), the rates of appearance for Ra2, Ra3, and Ra6 were 3.23 +/- 0.56, 2.64 +/- 0.50, and 2.00 +/- 0.27 mg/kg X min, respectively, whereas those in the hypothyroid subjects (T4 = 1.0 +/- 0.8 microgram/dl; n = 5) were 1.77 +/- 0.56 (P less than 0.01), 1.52, 1.57 +/- 0.31 (P less than 0.05) mg/kg X min, respectively. Conversely, the rates of appearance for Ra2 and Ra6 in the hyperthyroid subjects (T4 = 23.9 +/- 3.6 micrograms/dl) were 3.94 +/- 0.43 (P less than 0.05) and 2.54 +/- 0.22 (P less than 0.02), respectively, compared with the normal subjects. On the basis of these data, we noted that the normal subjects had a combined SCR of 1.23 +/- 0.35 mg/kg X min. In contrast, the hypothyroid patients had a significantly decreased combined SCR, 0.20 +/- 0.54 mg/kg X min (P less than 0.02). The hyperthyroid patients had a combined SCR of 1.39 +/- 0.23 mg/kg X min (P less than NS). To determine whether these cycles responded to thyroid hormone treatment, these same hypothyroid subjects were acutely treated for 1 wk with parenteral 50 micrograms/d sodium L-triiodothyronine and chronically with 100-150 micrograms/d L-thyroxine. After 7 d, their mean oxygen consumption rate and carbon dioxide production rate increased significantly from 102+/-13 micromol/kg.min, to 147+/-34 micromol/kg.min (P<0.05), and from 76+/-13 micromol/kg.min to 111+/-19 micromol/kg.min (P<0.05), respectively. The combined SCR (Ra(2)--Ra(6) remained unchanged at 0.07+/-0.37 mg/kg.min. However, after 6 mo of oral L-thyroxine therapy (T(4)=9.5+/-1.4 microgram/kl) the treated hypothyroid patients had increased their combined SCR (Ra(2)--Ra(6)) to 0.86 +/-0.23 mg/kg.min (P<0.02), a value not significantly different from the combined SCR of normal subjects. We conclude that substrate cycling between glucose and glucose-6-phosphate and between fructose-6-phosphate and fructose-1,6-diphosphate occurs in man and is affected by thyroid hormone. Substrate cycles may represent a mechanism by which thyroid hormone alters the sensitivity of certain reactions to metabolic signals.